Realizing Anapole-FP Cavity Strong Coupling in a Silicon-Based Metasurface Hybrid System - Wei Liu; Yu Tang; Zhengqi Liu; Junjie Li; Yang Cheng; Guiqiang Liu (IEEE Photonics Journal)
Manipulation of light-matter interactions has great potential applications in optical modulators and optical switches. However, the strong coupling of anapole-cavity modes has not been involved yet. Here, we firstly propose a simple Si-based metasurface hybrid system to realize tunable strong coupling of anapole-Fabry-Pérot (FP) cavity via inserting a Si square nanocubes metasurface inside an FP nanocavity. A remarkable spectral splitting behavior is achieved with large Rabi splitting of 192 meV due to the strong resonant coupling between the anapole and FP cavity modes. The induced two hybrid energy states are respectively dominated by the anapole mode and cavity mode and can be tuned by the length of FP nanocavity and the thickness of SiO2 spacer, respectively. This Si-based metasurface system opens an avenue for designing optoelectronic devices that can manipulate light-matter interactions at nanoscales.